Control by one drop of solvent: selective preparation of guest release/trap-triggered interconvertible molecular crystals. Issue 67 (22nd July 2020) - Yakiyama, Yumi; Fujinaka, Takahisa; Nishimura, Mio; Seki, Ryotaro; Sakurai, Hidehiro
Abstract : The selective preparation of two molecular crystals of the 4-pyridyl-1, 3-indanedione dimer, which are interconvertible by guest trapping/release, was achieved. Abstract : Interconvertible molecular crystals 1 close and 1 open composed of 4-pyridyl-1, 3-indanedione dimer 1 were selectively obtained. Thermal removal of solvent molecules in 1 open afforded 1 close . Further dipping of 1 close in a specific solvent reproduced 1 open . No crystallinity loss was observed even though both processes involved a drastic change of molecular packing arrangements.